2018
DOI: 10.1128/aem.01091-18
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of CYP505D6, a Self-Sufficient Cytochrome P450 from the White-Rot Fungus Phanerochaete chrysosporium

Abstract: The activity of a self-sufficient cytochrome P450 enzyme CYP505D6 from the lignin-degrading basidiomycete was characterized. Recombinant CYP505D6 was produced in and purified. In the presence of NADPH, CYP505D6 used a series of saturated fatty alcohols with C9-18 carbon chain lengths as substrates. Hydroxylation occurred at ω-1 to ω-6 positions of such substrates with C9-15 carbon chain lengths, except for 1-dodecanol, which was hydroxylated at ω-1 to ω-7 positions. Fatty acids were also substrates of CYP505D6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…Recently, Sakai et al. reported that CYP505D6, a self‐sufficient P450 from the white‐rot fungus Phanerochaete chrysosporium , preferably hydroxylates 1‐dodecanol and dodecanoic acid at the sub‐terminal positions (ω‐1 to ω‐3), but also yielded the in‐chain hydroxylated products (ω‐4 to ω‐7) as minor products . However, to date, no catalysts have been described for the regioselective in‐chain oxyfunctionalization of n ‐alkanes, where no directing functional group is available.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Sakai et al. reported that CYP505D6, a self‐sufficient P450 from the white‐rot fungus Phanerochaete chrysosporium , preferably hydroxylates 1‐dodecanol and dodecanoic acid at the sub‐terminal positions (ω‐1 to ω‐3), but also yielded the in‐chain hydroxylated products (ω‐4 to ω‐7) as minor products . However, to date, no catalysts have been described for the regioselective in‐chain oxyfunctionalization of n ‐alkanes, where no directing functional group is available.…”
Section: Methodsmentioning
confidence: 99%
“…Vanillin solutions and the hydrolysates (500 μL) were lyophilized, trimethylsilylated using 50 μL of N-methyl-N-trimethylsilyltrifluoroacetamide (Wako Pure Chemical Industries), and analysed using gas chromatography-mass spectrometry (GC-MS; GCMS-QP2010; Shimadzu, Kyoto, Japan) on a system equipped with a J&W DB-5MS capillary column (30 m × 0.25 mm i.d. × 0.25 μm thickness; Agilent Technologies, Santa Clara, CA) [62]. Glycine (at a final concentration of 50 μM) was used an internal standard for quantitative analysis using GC-MS. We determined the reducing sugar content in the hydrolysates obtained from alkaline-pretreated rice straw with or without oxygenradical and cellulase treatments following filter sterilization.…”
Section: Methodsmentioning
confidence: 99%
“…The Phanerochaete chrysosporium commonly known as white rot fungi 16 is well known for digestion of fragrant poisons, lignin and lipids and remediation of various pollutants such as PAH, heavy metals and dyes 17 . Phanerochaete chrysosporium is considered an uncommon organism for its capacity to depolymerize and change lignin, cellulose and hemicellulose, in comparison with different basidiomycetes 18 .…”
Section: Discussionmentioning
confidence: 99%